2017
DOI: 10.1111/ane.12769
|View full text |Cite
|
Sign up to set email alerts
|

Sleep convulsive seizures predict lack of remission in genetic generalized epilepsies: A retrospective study from a single epilepsy center in Egypt

Abstract: Prolonged remission of GGEs is high and compatible with treatment discontinuation. Sleep seizures are negative prognostic predictors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…Sillanpää and Schmidt also stated that patients with cluster of seizures are more liable for drugresistant epilepsy [12]. Nocturnal seizures were statistically significant for an unfavorable outcome in our study, similarly, a large epilepsy center in Cairo had concluded that sleep convulsive seizure was an independent predictor of lack of 5 years remission in patients with genetic generalized epilepsy [13].…”
Section: Discussionsupporting
confidence: 75%
“…Sillanpää and Schmidt also stated that patients with cluster of seizures are more liable for drugresistant epilepsy [12]. Nocturnal seizures were statistically significant for an unfavorable outcome in our study, similarly, a large epilepsy center in Cairo had concluded that sleep convulsive seizure was an independent predictor of lack of 5 years remission in patients with genetic generalized epilepsy [13].…”
Section: Discussionsupporting
confidence: 75%